Diagnostic value of blue laser imaging combined with magnifying endoscopy for precancerous and early gastric cancer lesions - Zhenming, Yang; Lei, Shen (Turkish Journal of Gastroenterology, 2019)
Abstract Background/Aims: Blue laser imaging (BLI) is a new technique for detailed examination of upper gastrointestinal lesions. This study aimed to evaluate the diagnostic value of BLI combined with magnifying endoscopy for precancerous and early gastric cancer lesions. Materials and Methods: A total of 249 gastric lesions detected via conventional white light endoscopy (WLE) based on assessments of mucosal shape and color were included in this study. The accuracy of diagnosis of precancerous or early cancer lesions white light magnification alone, BLI-contrast magnification, and BLI-bright magnification was determined according to the VS criteria. Results: For white light magnification alone, BLI-contrast magnification, and BLI-bright magnification, the concordance rates for lesions were 76.7%, 85.1%, and 86.7%, respectively, and the Kappa values were 0.571, 0.730, and 0.760, respectively. For the screening of high-grade intraepithelial neoplasia or early gastric cancer, the diagnostic sensitivities of white light magnification alone, BLI-contrast magnification, and BLI-bright magnification were 72.0%, 92.0%, and 92.0%, respectively; the specificities were 95.5%, 98.2%, and 99.1%, respectively; the consistencies were 93.2%, 97.6%, and 98.4%, respectively; and the Kappa values were 0.642, 0.871, and 0.911, respectively. For diagnoses of high-grade intraepithelial neoplasia or early gastric cancer, the concordance between endoscopic and pathological diagnosis was significantly higher for BLI-contrast and BLI-bright magnification than for white light magnification alone (p Conclusion: BLI combined with magnifying endoscopy may improve diagnostic accuracy for early gastric cancer and precancerous lesions. Cite this article as: Zhenming Y, Lei S. Diagnostic value of blue laser imaging combined with magnifying endoscopy for precancerous and early gastric cancer lesions. Turk J Gastroenterol 2019; 30(6): 549-56.